Sistem Informasi Pengadaan Pupuk Berbasis Web - Hutahaean, Jeperson (Building of Informatics, Technology and Science (BITS), 2019)
In supporting plantation operations, one of the obstacles faced by plantations is the processing system for palm oil principal inventory data, fertilizer dosage data and fertilizer demand data which are still done manually, resulting in delays in processing fertilizer realization and takes a long time. This research began with several methods, namely (interviews) directly to the speakers, field studies, literature studies and direct observations of the system created. This study aims to make it easier for management to see the availability of stock of goods from manuals to computerized systems using web-based systems, this system is closely related to computer media, hoping this system can produce information easily, quickly and accurately. Information system processing data for palm oil principal inventory, fertilizer dosage data and fertilizer demand data which are still done manually causes delays in processing fertilizer realization data processing, by using a system designed the information system processing data for principal oil palm inventory, fertilizer dosage data and data fertilizer needs can help agencies in processing data quickly, precisely, and accurately.